Orthogonal validation of PROTAC mediated degradation of the integral membrane proteins EGFR and c-MET - Camilla Ruffilli; Sascha Röth; Noam Zelcer; Kevin Moreau (Scientific Reports)
Abstract Dysregulation of integral membrane proteins (IMPs) has been linked to a myriad of diseases, making these proteins an attractive target in drug research. Whilst PROTAC technology has had a significant impact in scientific research, its application to IMPs is still limited. Limitations of the traditional approach of immunoblotting in PROTAC research include the low throughput compared to other methods, as well as a lack of spatial information for the target. Here we compare orthogonal antibody based approaches, i.e. immunoblotting, flow cytometry and immunofluorescence, to measure PROTAC mediated degradation of two established, endogenous targets, epidermal growth factor receptor (EGFR) and hepatocyte growth-factor receptor (c-MET). We discuss advantages and limitations of each methodology for the assessment of PROTAC efficacy on IMPs. Overall, we recommend the use of immunofluorescence and flow cytometry, for an increased accuracy with both a qualitative and quantitative insight into degradation efficacy and a critical distinction between cell membrane-localized and intracellular IMP protein pools.